2022
DOI: 10.3389/fpsyg.2022.908309
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Data Vulnerability in Online Health Communities: An Institutional Assurance Perspective

Abstract: In the last few years, online health communities (OHCs) have experienced rapid development due to advances in technology and the COVID-19 pandemic. However, the sensitive nature of medical information has also raised concerns from users about their privacy and reduced their intention to use OHCs. Considering the critical role of data privacy, this study explored the effect of data vulnerability on OHC users. Using online survey data collected from 438 OHC users in China, we found that data vulnerability signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…Data vulnerability refers to customers' feelings of being susceptible to harm because their personal data is possessed by firms [25,50]. The data management practices of firms, which include collecting, storing, and using customer data, are likely to trigger this negative perception [25].…”
Section: Data Vulnerabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Data vulnerability refers to customers' feelings of being susceptible to harm because their personal data is possessed by firms [25,50]. The data management practices of firms, which include collecting, storing, and using customer data, are likely to trigger this negative perception [25].…”
Section: Data Vulnerabilitymentioning
confidence: 99%
“…Thus, omnichannel shopping, by generating various types of customer data, may result in data vulnerability for customers. Research has suggested that data vulnerability can directly reduce trust [25], the perceived effectiveness of privacy policies [51], and psychological comfort [50]. Thus, a high level of data vulnerability creates a boundary turbulence situation, which may influence the relationships between omnichannel firms and their customers [52].…”
Section: Data Vulnerabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Second, X-Rays images are often shared in OHC. These images not only show tissues and structures inside the human body, but also contain the patient's sensitive information such as name, age, and sex [47,85]. Third, users may attach an image of the body part (e.g., faces, hands) with the post to show the current condition of infections or diseases.…”
Section: How Does Ohc Work?mentioning
confidence: 99%
“…These sites connect patients with caregivers, physicians, clinicians, nurses, and even other individuals (non-healthcare-workers) to share their medical problems and seek experts' suggestions [41]. To describe their symptoms, people often share information about their family history, medical history, and images of relevant testing results on these websites [47].…”
Section: Introductionmentioning
confidence: 99%